2014
DOI: 10.4238/2014.july.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of vascular endothelial growth factor polymorphisms in the survival of renal cell carcinoma patients

Abstract: ABSTRACT. We conducted a study to investigate the possible role of the vascular endothelial growth factor (VEGF) polymorphisms -2578C/A, -1154G/A and -634C/G and clinical factors in renal cell carcinoma (RCC) prognosis in a cohort of 336 RCC cases. A total of 336 patients with RCC were recruited from PLA General Hospital between January 2004 and December 2005. All patients were followed up until December 2010, and no patient was lost to follow-up. The follow-up time of this study was 60 months. At the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In ~33% of cases, patients with ccRCC are diagnosed with local or distant metastases due to its variable clinical presentation (7). In addition, there is a 40% recurrence rate in patients with ccRCC following surgery (8,9). Therefore, identifying novel therapeutic targets may improve the survival outcome and treatment response of patients with advanced ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…In ~33% of cases, patients with ccRCC are diagnosed with local or distant metastases due to its variable clinical presentation (7). In addition, there is a 40% recurrence rate in patients with ccRCC following surgery (8,9). Therefore, identifying novel therapeutic targets may improve the survival outcome and treatment response of patients with advanced ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…The most common sites of metastatic spread in RCC are the lung, bone, adrenal gland, liver and brain, whereupon more than one organ system is often involved in the metastatic process (3). In addition, RCC is relatively resistant to radiotherapy and chemotherapy, which result in the poor prognosis of patients with RCC with metastatic or recurrent disease and a 5-year survival rate of <20% (4). A number of studies have identified putative oncogenes involved in the carcinogenesis of RCC; however, the molecular mechanisms regulating the aggressive properties of RCC remain poorly understood (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that ~33% of patients with ccRCC displayed metastasis at diagnosis, resulting in poor prognosis and a low 5-year survival rate (14). However, previous studies have demonstrated the prognosis of RCC improves when the expression of a number of genes is targeted, including Tim-3 (15,16).…”
Section: Discussionmentioning
confidence: 99%